2015
DOI: 10.1007/s00217-015-2486-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition, antioxidant capacity, energy content and gastrointestinal stability of Croatian wild edible plants

Abstract: broom 40 % ethanolic extract. Phenolic acids of the three species were not stable during gastric and duodenal phases of simulated digestion. Two main black bryony kaempferol glycosides were best preserved after digestion (50 % of each). Black bryony contains more energy than wild asparagus and butcher's broom. Accordingly, we propose black bryony as a valuable source of antioxidant kaempferol glycosides with relevant gastrointestinal stability and higher energy content than so far more conventional vegetable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Asparagus species are considered as plants with antioxidant and immunostimulant properties (Negi, Singh, Joshi, Rawat, & Bisht, ). Besides steroidal saponins, as the major bioactive compounds, A. acutifolius contains flavonoids such as kaempferol, quercetin, and rutin (Poljuha et al, ) that contribute to the aforementioned biological effects. Results from our previous work (Poljuha et al, ), presented in Table , showed three major phenolic components of A. acutifolius : quercetin‐3‐ O ‐rutinoside (247.90 µg/ml), isorhamnetin‐3‐ O ‐rutinoside (156.10 µg/ml), and kaempferol‐3‐ O ‐rutinoside (12.40 µg/ml).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asparagus species are considered as plants with antioxidant and immunostimulant properties (Negi, Singh, Joshi, Rawat, & Bisht, ). Besides steroidal saponins, as the major bioactive compounds, A. acutifolius contains flavonoids such as kaempferol, quercetin, and rutin (Poljuha et al, ) that contribute to the aforementioned biological effects. Results from our previous work (Poljuha et al, ), presented in Table , showed three major phenolic components of A. acutifolius : quercetin‐3‐ O ‐rutinoside (247.90 µg/ml), isorhamnetin‐3‐ O ‐rutinoside (156.10 µg/ml), and kaempferol‐3‐ O ‐rutinoside (12.40 µg/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Besides steroidal saponins, as the major bioactive compounds, A. acutifolius contains flavonoids such as kaempferol, quercetin, and rutin (Poljuha et al, ) that contribute to the aforementioned biological effects. Results from our previous work (Poljuha et al, ), presented in Table , showed three major phenolic components of A. acutifolius : quercetin‐3‐ O ‐rutinoside (247.90 µg/ml), isorhamnetin‐3‐ O ‐rutinoside (156.10 µg/ml), and kaempferol‐3‐ O ‐rutinoside (12.40 µg/ml). R. aculeatus L. is a very ancient therapeutic plant, extensively used for the treatment of chronic venous insufficiency, varicose veins, and haemorrhoids (Masullo, Pizza, & Piacente, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al (2007) found that the total phenol content of asparagus (A. officinalis) in acetone, methanol and aqueous extract, was 5.0±0.5, 4.9±0.7, and 4.9±0.9 [mg catehin equivalent/g dry weight], respectively. The investigation of Istrian wild asparagus showed that the results for the 40% EtOH and 96% EtOH extract of wild asparagus were 793±33 mg GAE/100g DW and 181±26 mg GAE/100 g DW, respectively (Poljuha et al, 2015). Very high content of phenolic compounds was found in the Portuguese wild asparagus:…”
Section: Figure 1 Total Polyphenol Content In Wild (A Acutifolius Lmentioning
confidence: 97%
“…From the foregoing, it can be concluded that the phenolic profile of populations from different geographical areas varies considerably (Poljuha et al, 2015). However, large differences can M. Palfi et al: TOTAL POLYPHENOL CONTENT AND ANTIOXIDANT ACTIVITY WILD AND ... be partly explained by various analysis modifications both in the extraction of polyphenols and in the results.…”
Section: Figure 1 Total Polyphenol Content In Wild (A Acutifolius Lmentioning
confidence: 99%